Advanced functionalized asphalt. Texture and optical non-invasive microtopographic characterization - Costa, Manuel F. M. (2023)
The incorporation of electrochromic elements onto asphalt mixture or the application of advanced coating can improve the performance of asphalt and allow a reduced environmental impact of vehicle circulation. A brief overview will be given. The inspection and characterization of the texture of rough surfaces, like most of the ones that can be found in pavements, it’s a difficult and complex process. The success of the process is highly dependent not only on the metrological tolerances but also on the particular characteristics of the surface, both physical and compositional but also on what concerns its tridimensionality. In this communication we will also give a brief overview of most common surface texture inspection methods focusing of optical and non-contact/non-invasive ones.